One‐Pot Enzymatic Cascade for Toxicant Degradation and Sugar Acid Production - Pongsupasa, Vinutsada; Punthong, Pangrum; Chaiyen, Pimchai; Wongnate, Thanyaporn (Chembiochem : a European journal of chemical biology, 2024)
This study introduces a novel one‐pot enzymatic cascade approach for converting toxicants and continuously generating an electron acceptor for production of sugar acids. This method offers a promising solution to concerns about pesticide toxicity and environmental contamination by transforming hazardous substances into a useful electron acceptor. This acceptor is then utilized to produce valuable chemicals with broad industrial applications, particularly in the food and pharmaceutical sectors. The cascade reaction employs organophosphate hydrolase (OPD) to convert pesticides into 4‐nitrophenol (4‐NP), which is subsequently transformed into 1,4‐benzoquinone by HadA monooxygenase (HadA). 1,4‐benzoquinone serves as an electron acceptor in the catalysis of sugar acid formation via pyranose dehydrogenase (PDH). The results indicate that this cascade reaction effectively converts lactose to lactobionic acid and xylose to 2‐keto‐xylonic acid. The latter can be further processed into xylonic acid through NaBH4 reduction. Notably, the one‐pot reaction yields up to 10 % higher compared to the direct addition of 1,4‐benzoquinone. The synthesized xylonic acid exhibits exceptional water uptake properties in hydrogels, and the synthesized lactobionic acid shows antioxidant activity comparable to well‐established antioxidants. These findings demonstrate the technological viability of these reaction cascades for various applications. A one‐pot biocatalytic cascade for sugar acid production not only breaks down hazardous chemicals and generates benzoquinone but also enhances antioxidant activity and water uptake in hydrogels. This is achieved through the coordinated action of multiple enzymes, including organophosphate hydrolase (OPD), HadA monooxygenase (HadA), thermostable flavin reductase (C1‐A58P), Bacillus simplex formate dehydrogenase (BsFDH), and pyranose dehydrogenase (PDH).